Mendobrak Diskriminasi Lesbian Gay, Bisexual, Transgender (LGBT) dalam Bingkai Agama dan Kesetaraan Gender - Daniel Tri Juniardo Tambunan (Institut Agama Kristen Negeri Tarutung, 2021)
Abstract:This paper is intended to address the problems of lesbians, gays, bisexual, transgender or commonly called LGBT. LGBT behavior is widely addressed to people's lives and very often receives disintegration behavior in religious and social life. The basic problem is that LGBT lack of status among communities and that LGBT is receiving violence and discrimination within communities. LGBT people always get the negative view and stigma and hate of society. From a religious perspective and gender equality, the LGBT are marginalized. Because of that, LGBT problem needs attention in frame and gender equality in order to break the bullying of LGBT people. This paper provide by religious sociology and gender equality perspective to see LGBT rights. Using literacy study, through the study and/or exploration of various journals, books, research results, and documents (both print and electronic), and other data and/or information that perl deemed relevant to the study. The goal of this writing is to force LGBT discrimination in the frame of religion and gender equality.Keywords: LGBT, gender equality, religion Abstrak:Tulisan ini bertujuan untuk menjawab persoalan kaum Lesbian, Gay, Bisexual, Transgender atau yang sering disebut dengan LGBT. Perilaku kaum LGBT banyak disoroti dalam kehiduapn masyarakat dan sangat sering mendapatkan perilaku diskrimasi dalam kehidupan agama dan masyarakat. Permasalahan mendasar adalah tidak adanya kedudukan LGBT ditengah masyarakat sehingga kaum LGBT mendapatkan kekerasan dan diskriminasi di dalam masyarakat. Kaum LGBT selalu mendapatkan pandangan dan stigma negatif serta kebencian dari masyarakat. Dari perspektif agama dan kesetaraan gender, kaum LGBT adalah kaum yang termarginalkan. Oleh karena itu menyikapi permasalahan tersebut LGBT perlu mendapatkan perhatian dalam bingkai dan kesetaraan gender dalam rangka mendobrak diskrimasi kepada kaum LGBT. Penelitian ini menggunakan pendekatan sosiologi agama dan kesetaraan gender untuk melihat Hak-hak kaum LGBT. Penelitian ini menggunakan pendekatan penelitian kepustakaan, dengan pengumpulan data melalui telaah dan/atau eksplorasi berbagai jurnal, buku, hasil penelitian, dan dokumen (baik cetak maupun elektronik), serta sumber data dan/atau informasi lain yang dianggap perl relevan dengan studi. Tujuan tulisan ini hendak mendobrak diskriminasi kaum LGBT dalam bingkai agamadan kesetaraan gender.Kata kunci: LGBT, kesetaraan gender, agama